Перестройка фронтов квазипродольных и квазипоперечных нестационарных волн в неоднородных трансверсально-изотропных упругих средах - Гуляев, В.И.; Луговой, П.З.; Заец, Ю.А.; Набиль, М. (Прикладная механика, 2011)
A problem on propagation and rearrangement of fronts of discontinuous waves in inhomogeneous transversally isotropic elastic media is considered. A technique of constructing the evolable system of rays and fronts is proposed. The cases of forming the geometrical singularities on the front surfaces are studied for different values of parameters of elastic medium anisotropy and inhomogeneity.